Wie vereinfacht man # (1 / h ^ -2) ^ - 1 * h ^ 3 #?

Antworten:

# h #

Erläuterung:

In Anbetracht dessen

# (1 / h ^ {- 2}) ^ {- 1} cdot h ^ 3 #

# = (h ^ {- 2}) ^ {1} cdot h ^ 3 #

# = h ^ {- 2} cdot h ^ 3 #

# = h ^ {- 2 + 3} #

# = h #

Antworten:

# h #

Erläuterung:

Gegeben: # (1 / h ^ -2) ^ - 1 * h ^ 3 #

Verwenden Sie die Exponentenregeln: # 1 / x ^ -n = x ^ n; "" x ^ -m = 1 / x ^ m #

# (x ^ m) ^ n = x ^ (m * n); "" x ^ nx ^ m = x ^ (n + m) #

# (1 / h ^ -2) ^ - 1 * h ^ 3 = (h ^ 2) ^ - 1 * h ^ 3 = h ^ -2 * h ^ 3 #

#h ^ (- 2 + 3) = h ^ 1 = h #